INTERFERENSI FONOLOGIS BAHASA INDONESIA DALAM PELAFALAN ONSET GUGUS KONSONAN KATA BAHASA JAWA - Putri Aryan Dini (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2021)
ABSTRAK This study aims to determine the form of interference that may occur in Indonesian speakers who pronounce Javanese words with complex onset consonant clusters and to see if the interference omit the meaning of the word. This research method is to analyze the recording of the reading test by two research subjects using PRAAT software. There are two interferences produced by the research subjects, namely epenthesis schwa and deletion. The results of the perception test show that schwa epenthesis interference is unacceptable but does not omit the meaning, while deletion is unacceptable and omit the meaning. Both of these interferences are a form of adaptation of research subjects in pronouncing the complex onset consonant clusters that are not prevalent in Indonesian. Kata Kunci: phonotactics, interference, onset consonant cluster